Peran Kejaksaan dalam Penegakan Hukum Pidana Illegal,Unreported,and Unregulated Fishing (Studi Kasus Konflik Maritim di Zona Ekonomi Eksklusif Indonesia) - Sitirahmah, Noni; Putri dini, Mayla (Pusat Strategi Kebijakan Penegakan Hukum, Kejaksaan Agung, 2025)
This study examines legal and sovereignty issues arising from the practice of Illegal, Unreported, and Unregulated (IUU) Fishing in Indonesia’s Exclusive Economic Zone (ZEE). Such activities pose serious challenges to Indonesia’s sovereignty and maritime law enforcement. The main problems lie in weak inter-agency coordination and the limited academic focus on the role of the Prosecutor’s Office. Using a qualitative method with a juridical-normative approach, this research analyzes national and international legal documents, as well as case studies of the 2020 North Natuna Sea incident and the 2022 arrest of Vietnamese vessels. The findings reveal overlapping authority among the Indonesian Navy, the National Police, the Ministry of Marine Affairs and Fisheries, the Maritime Security Agency (Bakamla), and the Prosecutor’s Office, undermining law enforcement effectiveness. The study recommends institutional reform, integrated protocols, and capacity building for public prosecutors in maritime affairs.